Factors Affecting Pregnant Women in Preparation of Early Breastfeeding Initiation (IMD) at Grobogan Regencys (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
Exclusive breastfeeding will be realized if mother start implementing Early Breastfeeding Initiation (IMD) program. The purpose of this study is to investigate factors influencing pregnant women in preparation for early breastfeeding initiation (IMD) in Grobogan regency. Study method is quantitative with cross-sectional design. Total population is 716 pregnant women with minimal of 85 sample after calculations. To anticipate drop out, 100 samples will be collected. Independent variable is the factors influencing preparation of IMD in pregnant women and dependent variable is preparation of Early Breastfeeding Initiation (IMD). Data was analyzed using multiple logistic regression. The analysis showed no significant relation between factors such as education, knowledge, attitudes, breastfeeding experience, husband/family support, participation in classes of pregnant women, the role of health workers with preparation for IMD. In contrast, the variable trust had a significance value of 0.001 0.05. We conclude that IMD preparation of pregnant women is most influenced by trust.